Hubungan Klasifikasi Perokok dengan Kesehatan Jaringan Periodontal Masyarakat yang Merokok di Pulau Harapan diukur dengan Skor CIPTN - Baby Prabowo; Triyawati Rosida; Hidayati Ahmad (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
The Ministry of Health in Alamsyah, (2017) states that smoking behavior is an activity of burning one of the tobacco products, then smoking or inhaling the smoke, including clove cigarettes, white cigarettes, cigars or other forms produced from the nicotina tabacum, nicotina rustica and other species. The classification of smokers consists of: light smokers (1-4 cigarettes/day), moderate smokers (5-14 cigarettes/day), heavy smokers (> 15 cigarettes/day). This study was conducted to obtain an overview of the health of the periodontal tissue in people who smoke on the island of Harapan. Data were collected by classifying smokers and intra-oral examination of CPITN on every community who smoked on the island of Harapan whose results were recorded on the examination sheet. This examination was carried out in January 2020. The data were analyzed by Univariate and Bivariate. Based on the results of research on male smokers in Harapan Island, Seribu Islands region, it can be concluded that there are no smokers who have a score of 0 or have healthy periodontal tissue. In the category of moderate smokers, the highest number of CIPTN 2 scores or had tartar on the sub gingiva was 9 people (52.9%), while in the heavy smoker group the highest score also had CIPTN 2 scores or had tartar on the sub gingiva as many as 18 people (48,6%). The statistical test results obtained P = 0.029 where the P value <0.05, it can be concluded that there is a difference in the proportion of the classification of smokers to the state of the periodontal tissue calculated based on the CIPTN status or there is a significant relationship between the classification of smokers and the state of the periodontal tissue calculated by the CIPTN score).